2016
DOI: 10.1016/j.immuni.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Regulation of Two Type I Interferon Signaling Pathways in Plasmacytoid Dendritic Cells Controls Anti-malaria Immunity and Host Mortality

Abstract: Type I interferon (IFN) is critical for controlling pathogen infection; however, its regulatory mechanisms in plasmacytoid cells (pDCs) still remain unclear. Here, we have shown that nucleic acid sensors cGAS-, STING-, MDA5-, MAVS-, or transcription factor IRF3-deficient mice produced high amounts of type I IFN-α and IFN-β (IFN-α/β) in the serum and were resistant to lethal plasmodium yoelii YM infection. Robust IFN-α/β production was abolished when gene encoding nucleic acid sensor TLR7, signaling adaptor MyD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
183
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(197 citation statements)
references
References 37 publications
12
183
2
Order By: Relevance
“…During viral infection, the TLR9-myeloid differentiation primary response 88 (MYd88)-IRF3/7 pathway is necessary for mouse monocytes recruitment to lymph nodes, whereas the STING pathway is necessary for local production of type-I IFN (112). However, STING signaling can induce suppressor of cytokine signaling1 (SOCS1) expression, which can negatively regulate MyD88 activity (113) (Figure 3C).…”
Section: Cross-regulation Of the Cgas-sting Pathway With Other Dna-sementioning
confidence: 99%
“…During viral infection, the TLR9-myeloid differentiation primary response 88 (MYd88)-IRF3/7 pathway is necessary for mouse monocytes recruitment to lymph nodes, whereas the STING pathway is necessary for local production of type-I IFN (112). However, STING signaling can induce suppressor of cytokine signaling1 (SOCS1) expression, which can negatively regulate MyD88 activity (113) (Figure 3C).…”
Section: Cross-regulation Of the Cgas-sting Pathway With Other Dna-sementioning
confidence: 99%
“…Furthermore, for parasite infections of the liver such as Plasmodium spp. there is important evidence on the importance of the IFN-α signaling (13,(179)(180)(181)(182). Due the regulatory interactions of IFN-α and IFN-λ and the clinical importance of relevant SNPs (31), it is not unreasonable to postulate an impact.…”
Section: Parasite and Fungal Infectionsmentioning
confidence: 99%
“…Activation of PRRs has at least two roles in host immunity during blood-stage malaria infection: (a) direct control of parasite replication and/or parasite killing via innate immune effector mechanisms and (b) generation of cues that expand and differentiate antigen-specific CD4 + T cells and B cells (3)(4)(5). It was recently reported that the PRR cyclic GMP-AMP synthase (cGAS) was a critical innate signal in the context of a murine model of lethal malaria (6). We used a nonlethal murine model of blood-stage malaria (Plasmodium yoelii 17XNL) to determine the role that cGAS plays in the generation of the humoral immune response and, specifically, immunologic memory.…”
Section: Introductionmentioning
confidence: 99%